PERBEDAAN KANDUNGAN BAHAN ORGANIK PADA TAHAH PASIR DAN TANAH LIAT SETELAH PENAMBAHAN PEMBENAH TANAH DARI BAHAN DASAR TUMBUHAN AKUATIK - Izzati, Munifatul (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
Organic matter in the soil is a key factor in determining soil fertility. Addition of soil conditioner is the best way to provide organic matter in the soil. The aim of this study is to analyze the effect of aquatic plants as source of soil conditioner on organic contain of sandy and clay soil. This study analyze as much as 17 species of aquatic plants either from fresh water, brackish water and marine plants. Results indicated that addition of soil conditioner from aquatic plants significantly increased organic contain either in sandy or clay soil (p<0,05). In sandy soil, the highest organic contain (917%) was provided by brackish water plants, Najas marina, whereas in Clay soil was provided by marine plant, Gracilaria verrucosa (220%) Keywords: Soil conditioner, aquatic plant, sandy, clay soil